2017
DOI: 10.3389/fimmu.2017.01748
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapy for Glioblastoma Multiforme by Restoring LRRC4 in Tumor Cells: LRRC4 Inhibits Tumor-Infitrating Regulatory T Cells by Cytokine and Programmed Cell Death 1-Containing Exosomes

Abstract: Glioblastoma multiforme (GBM) is a heterogeneous malignant brain tumor, the pathological incidence of which induces the accumulation of tumor-infiltrating lymphocytes (TILs). As a tumor suppressor gene, LRRC4 is absent in GBM cells. Here, we report that the recovery of LRRC4 in GBM cells inhibited the infiltration of tumor-infiltrating regulatory T cells (Ti-Treg), promoted the expansion of tumor-infiltrating effector T (Ti-Teff) cells and CD4+CCR4+ T cells, and enhanced the chemotaxis of CD4+CCR4+ T cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…At the time, progress was expected particularly for the EV-based immunotherapies [65][66][67]. When transported by EVs, this gene can ultimately inhibit the proliferation of regulatory T cells that infiltrate the tumour [68]. A few examples have already been reported in this review [48,50,62].…”
Section: Diagnosis and Therapymentioning
confidence: 97%
See 1 more Smart Citation
“…At the time, progress was expected particularly for the EV-based immunotherapies [65][66][67]. When transported by EVs, this gene can ultimately inhibit the proliferation of regulatory T cells that infiltrate the tumour [68]. A few examples have already been reported in this review [48,50,62].…”
Section: Diagnosis and Therapymentioning
confidence: 97%
“…The therapeutic mechanism is based on the re-expression, within these cancer cells, of leucine-rich repeat C4 (LRRC4), a tumour suppressor gene. When transported by EVs, this gene can ultimately inhibit the proliferation of regulatory T cells that infiltrate the tumour [68]. Another approach, already promising for in-vivo therapy of breast cancer, is based on the engineering of MSC cells competent for the release of EVs enriched in the microRNA, miR-379.…”
Section: Diagnosis and Therapymentioning
confidence: 99%
“…LRRC4 (Leucine-rich repeat-containing protein 4) is a transmembrane and cytoplasmic protein and plays an important role in neural development and malignant transformation of glioma (14)(15)(16)(17)(18). We had previously shown that LRRC4 binds to PAR6 and serves as a partner of PAR complex in the neuron polarity (14).…”
Section: Introductionmentioning
confidence: 99%
“…We had previously shown that LRRC4 binds to PAR6 and serves as a partner of PAR complex in the neuron polarity (14). LRRC4 deletion contributes to glioblastoma multiforme (GBM) malignant progression, while LRRC4 overexpression inhibits GBM cell proliferation and invasion by inhibiting the RTK/ERK/AKT/NF-kB signaling pathway (15)(16)(17)(18). LRRC4 binds to ERK1/2 directly and recruits ERK1/2 to the cytoplasm (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation